Metabolomic and transcriptomic analyses reveal MYB-Related genes involved in drought resistance in grafted potatoes via the flavonoid pathway - Yinqiao Jian; Chunyan Gao; Yangyang Shang; Junhong Qin; Shaoguang Duan; Chunsong Bian; Guangcun Li (Plant Stress)
Drought poses a significant challenge to global potato production. Grafting, a classical horticultural technique, has the potential to enhance resistance to both biotic and abiotic stresses. However, the use of grafting to improve drought resistance in potatoes, along with the underlying genetic and regulatory changes remains inadequately documented. In this study, we investigated the drought phenotypes, as well as the metabolomic and transcriptomic profiles of leaves and roots in self-grafted (drought-sensitive scion/ drought-sensitive rootstock, SS) and hetero-grafted (drought-sensitive scion/drought-tolerant rootstock, ST) potatoes. After 40 days, hetero-grafts exhibited greater drought resistance as well as lower dry matter content and higher soluble sugar content compared to self-grafts, indicating that grafting with drought-tolerant rootstocks can enhance the drought resistance of the scion and revealed physiological process. Metabolomic analysis revealed a significant enrichment of flavonoids, particularly in comparisons between SS-leaf vs. ST-leaf and SS-root vs. ST-root. Transcriptomic analysis further supported these findings, showing an enrichment in the biosynthesis of plant secondary metabolites in the same comparisons, aligning with metabolomic data. These differentially accumulated metabolites and expressed genes, particularly in SS-leaf vs. ST-leaf comparison, suggest a mechanism involving long-distance metabolites and mRNA in grafting-mediated drought resistance. Weighted Gene Co-expression Network Analysis identified the yellow module, which correlated with drought, and highlighted MYB or MYB-related genes as hub genes. Our results reveal global metabolomic and transcriptomic features associated with drought tolerance in potatoes, demonstrating that grafting can alter the composition and accumulation of genes and metabolites, leading to enhanced drought resistance. The significant role of flavonoids as modulators of drought resistance, supported by comprehensive transcriptomic and metabolomic analyses, underscores the pivotal regulatory function of the MYB-WD40-bHLH transcription factor complex in orchestrating the stress response.